STRES AKADEMIK DITINJAU DARI SELF-REGULATED LEARNING DAN STUDENT WELL-BEING PADA SISWA KELAS X DI SMKN 1 KARAWANG - Randwitya Ayu Ganis Hemasti; Puspa Rahayu Utami Rahman; Gina Kania Rumanti; Marhisar Simatupang (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to determine the effect of self-regulated learning and student well-being on student academic stress at SMK N 1 Karawang. In this study, there are three variables, namely self-regulated learning, student well-being, and academic stress. The major hypothesis of this study is that there is an effect of self-regulated learning and student well-being on students' academic stress at SMK N 1 Karawang. The number of samples used was 124 vocational students at SMK N 1 Karawang. Using purposive sampling method. The data method in this study uses quantitative methods. The analysis in this study uses multiple regression analysis using SPSS 22.0. Based on the test results, the hypothetical model has an outer loading value above 0.5 and Cronbach's alpha value for all constructs above 0.5. The results showed that there was an effect of self-regulated learning and student well-being on students' academic stress at SMK N 1 Karawang. The result of R Square in this study was 28.8%.